Statistical Λ-Convergence in Probabilistic Normed Spaces - M. Aldhaifallah; K. S. Nisar; H. M. Srivastava; M. Mursaleen (Journal of Function Spaces)
The main objective of the study was to understand the notion of Λ-convergence and to study the notion of probabilistic normed (PN) spaces. The study has also aimed to define the statistical Λ-convergence and statistical Λ-Cauchy in PN-spaces. The concepts of these approaches have been defined by some examples, which have demonstrated the concepts of statistical Λ-convergence and statistical Λ-Cauchy in PN-spaces. Previous studies have also been used to understand similar terminologies and notations for the extraction of outcomes.